A method for preparing tin-based perovskite battery

By adding carbohydrate to the perovskite precursor solution of the tin-based perovskite battery, the problems of instability and rough film surface of the tin-based perovskite battery are solved, and higher stability and photoelectric conversion efficiency are achieved.

CN115101681BActive Publication Date: 2025-03-28HUBEI UNIV OF ARTS & SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210619587.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-01
Publication Date
2025-03-28
Estimated Expiration
2042-06-01

AI Technical Summary

Technical Problem

Existing tin-based perovskite batteries are unstable, easily oxidized, and the film surface is rough.

Method used

By adding carbohydrazide to the perovskite precursor solution, Sn2+ ions are inhibited from oxidation, and the crystallization rate is adjusted to avoid roughening of the film surface.

Benefits of technology

The stability and service life of tin-based perovskite batteries are improved, and a smooth film layer and higher photoelectric conversion efficiency are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115101681B_ABST
    Figure CN115101681B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a tin-based perovskite battery, comprising the following steps: providing a hole transport layer on a conductive glass substrate; x MA 1‑x Pb y Sn 1‑y I 3 Add carbohydrazide to the solution to obtain a perovskite precursor solution; arrange a perovskite precursor layer on the hole transport layer; and arrange an electron transport layer, a buffer layer and a back electrode layer on the perovskite precursor solution layer from bottom to top. x MA 1‑x Pb y Sn 1‑ y I 3 Adding carbohydrazide to the solution can inhibit the oxidation of the perovskite precursor and can also regulate the crystallization rate, thereby preparing a perovskite precursor layer with a smooth surface, which is not easily oxidized and has good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic materials, and in particular to a method for preparing a tin-based perovskite battery. Background Art

[0002] Organic-inorganic hybrid perovskite solar cells have experienced rapid development for more than 10 years. Since they were first reported in 2009, their photoelectric conversion efficiency has reached 25.7% in 2022, reaching 95% of the efficiency of single-crystal silicon solar cells, and have excellent photoelectric performance. Their rapid development is attributed to their advantages such as simple preparation process, low production cost, adjustable band gap, high carrier diffusion length and high absorption coefficient. They are considered to be one of the candidate materials for high-efficiency solar cells (PSCs) and have potential application value in the photovoltaic field. However, the degradation products of lead-based perovskites are toxic to the environment, humans and other species, which greatly hinders the commercialization of this technology.

[0003] Therefore, non-toxic lead-free perovskite light absorbers have attracted much attention in recent years. Among them, tin is considered to be a less toxic alternative to lead, and chemical composition engineering of lead halide perovskites by partially or completely replacing toxic lead with tin has been widely reported as a feasible method. In addition, the optical bandgap range of tin-based perovskites is 1.2-1.4 eV, which is very close to the optimal bandgap width (1.34 eV) of the Shockley-Queisser (SQ) limit under the AM1.5 solar spectrum23. However, there are also two problems with tin-based PSCs: one is that the Sn in its precursor solution 2+ Sn is easily oxidized 4+ Moreover, after being prepared into thin films, they are extremely unstable in the air. Secondly, during the crystallization process of the thin film, the crystallization rate of Sn-based perovskite is too fast, resulting in a very rough surface of the film. How to provide a tin-based perovskite battery with good stability and a smooth film layer on the surface is a technical problem that needs to be solved urgently. Summary of the invention

[0004] The main purpose of the present invention is to propose a method for preparing a tin-based perovskite battery, aiming to solve the problems that the existing tin-based perovskite battery is unstable, easily oxidized and has a rough film surface.

[0005] To achieve the above object, the present invention provides a method for preparing a tin-based perovskite battery, and the method for preparing a tin-based perovskite battery comprises the following preparation steps:

[0006] A hole transport layer is provided on the conductive glass substrate;

[0007] To FA x MA 1-x Pb y Sn 1-yI3 solution is added with carbohydrazide to obtain a perovskite precursor solution, wherein 0 <x<1,0<y<1;

[0008] Disposing a perovskite precursor layer on the hole transport layer;

[0009] An electron transport layer, a buffer layer and a back electrode layer are sequentially arranged on the perovskite precursor solution layer from bottom to top to obtain a tin-based perovskite battery.

[0010] Optionally, the FA x MA 1-x Pb y Sn 1-y In the step of adding carbohydrazide to the I3 solution to obtain a perovskite precursor solution, the carbohydrazide and the FA x MA 1-x Pb y Sn 1-y The volume ratio of I3 solution is (0.01~0.03):1.

[0011] Optionally, the FA x MA 1-x Pb y Sn 1-y The steps of adding carbohydrazide to the I3 solution to obtain a perovskite precursor solution include:

[0012] Lead iodide, stannous iodide, formamidine hydroiodide and methyl iodide were dissolved in N,N-dimethylformamide and dimethyl sulfoxide, and shaken for 2 to 2.5 hours under protective gas to obtain FA x MA 1-x Pb y Sn 1-y I3 solution, to the FA x MA 1-x Pb y Sn 1-y Carbohydrazide is added to the I3 solution to obtain a perovskite precursor solution.

[0013] Optionally, the protective gas includes nitrogen.

[0014] Optionally, the step of providing a perovskite precursor layer on the hole transport layer comprises:

[0015] A perovskite precursor solution is dripped onto the hole transport layer, and the solution is spin-coated at a speed of 1000 to 1500 rpm for 10 to 15 s, an anti-solvent is dripped, and the solution is spin-coated at a speed of 3500 to 4000 rpm for 20 to 30 s. The solution is annealed at 100 to 110° C. for 10 to 15 min to form a perovskite precursor layer on the hole transport layer.

[0016] Optionally, the anti-solvent comprises chlorobenzene and / or ethyl acetate.

[0017] Optionally, the step of providing a hole transport layer on the conductive glass substrate includes:

[0018] The conductive glass substrate is cleaned with a solvent, treated in an ultraviolet ozone environment for 15 to 20 minutes, PEDOT:PSS (Al 4083) is spin-coated on the conductive glass substrate at a rotation speed of 3500 to 4000 rpm, and annealed at 140 to 150° C. for 10 to 15 minutes to form a hole transport layer on the conductive glass substrate.

[0019] Optionally, the solvent includes any one of acetone, isopropanol, ethanol and ultrapure water.

[0020] Optionally, the step of sequentially disposing an electron transport layer, a buffer layer and a back electrode layer on the perovskite precursor solution layer from bottom to top comprises:

[0021] An electron transport layer is evaporated on the perovskite precursor solution layer using an organic evaporator. After cooling, a buffer layer is evaporated on the electron transport layer using an organic evaporator. After cooling, a back electrode layer is evaporated on the buffer layer using a metal evaporator to obtain a tin-based perovskite battery.

[0022] Optionally, the material of the electron transport layer includes C60; and / or,

[0023] The material of the buffer layer includes 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline; and / or,

[0024] The material of the back electrode layer includes Ag.

[0025] The technical solution provided by the present invention has a simple preparation method and is easy to operate. The tin-based perovskite battery prepared by the method has higher stability, longer service life and higher conversion efficiency. In the preparation process, carbohydrazide is doped into the perovskite precursor solution to inhibit the Sn in the perovskite precursor solution. 2+ It is oxidized by air oxides, thereby improving the stability of the prepared tin-based perovskite battery and extending its service life. At the same time, the amino and carbonyl groups of the carbohydrazide can also react with the free Sn in the perovskite precursor solution. 2+ and free Pb 2+ The interaction between ions can regulate the crystallization rate and prevent the perovskite precursor layer from crystallizing too quickly, which would result in a rough surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0027] Figure 1 A schematic diagram of a process of an embodiment of a method for preparing a tin-based perovskite battery provided by the present invention;

[0028] Figure 2 This is a diagram of the perovskite precursor solution prepared in step (2) of Example 1 of the present invention and the perovskite precursor solution prepared in the comparative example after being placed in the air for 24 hours (the left side is Example 1, and the right side is Example 2);

[0029] Figure 3 This is a SEM cross-sectional view of the perovskite precursor layer prepared in step (3) of Example 1 of the present invention;

[0030] Figure 4 This is a SEM cross-sectional view of the perovskite precursor layer prepared in step (3) of the comparative example of the present invention;

[0031] Figure 5 This is a SEM image of the perovskite precursor layer prepared in step (3) of Example 1 of the present invention after being exposed to air for 5 days;

[0032] Figure 6 This is a SEM image of the perovskite precursor layer prepared in step (3) of the comparative example of the present invention after being exposed to air for 5 days;

[0033] Figure 7 IV curves of the tin-based perovskite battery prepared in Example 1 of the present invention and the tin-based perovskite battery prepared for comparison;

[0034] Figure 8 XRD diagrams of the perovskite precursor layer prepared in step (3) of Examples 1 to 5 of the present invention and the perovskite precursor layer prepared in step (3) of the comparative example;

[0035] Fig. 9 This is a SEM image of the perovskite precursor layer prepared in step (3) of Example 1 of the present invention;

[0036] Fig.10 This is a SEM image of the perovskite precursor layer prepared in step (3) of Example 2 of the present invention;

[0037] Fig.11 This is a SEM image of the perovskite precursor layer prepared in step (3) of Example 3 of the present invention;

[0038] Fig.12 This is a SEM image of the perovskite precursor layer prepared in step (3) of Example 4 of the present invention;

[0039] Fig.13 This is a SEM image of the perovskite precursor layer prepared in step (3) of Example 5 of the present invention;

[0040] Fig.14 This is a SEM image of the perovskite precursor layer prepared in step (3) in the comparative example of the present invention.

[0041] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0042] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.

[0043] After more than 10 years of rapid development, organic-inorganic hybrid perovskite solar cells have achieved a photoelectric conversion efficiency of 25.7% since their first report in 2009, reaching 95% of the efficiency of single-crystal silicon solar cells in 2022, with excellent photoelectric performance. Its rapid development is attributed to its advantages such as simple preparation process, low production cost, adjustable band gap, high carrier diffusion length and high absorption coefficient. It is considered to be one of the candidate materials for high-efficiency solar cells (PSCs) and has potential application value in the photovoltaic field. However, the degradation products of lead-based perovskites are toxic to the environment, humans and other species, which greatly hinders the commercialization of this technology. Therefore, non-toxic lead-free perovskite light absorbers have attracted much attention in recent years. Among them, tin is considered to be a less toxic substitute for lead, and the chemical composition engineering of preparing lead halide perovskites by partially or completely replacing toxic lead with tin has been widely reported as a feasible method; there are two problems with existing tin-based perovskite cells: one is that the Sn in its precursor solution 2+Sn is easily oxidized 4+ Moreover, after being prepared into thin films, they are extremely unstable in the air. Secondly, during the crystallization process of the thin film, the crystallization rate of Sn-based perovskite is too fast, resulting in a very rough surface of the film. How to provide a tin-based perovskite battery with good stability and a smooth film layer on the surface is a technical problem that needs to be solved urgently.

[0044] In view of this, the present invention provides a method for preparing a tin-based perovskite battery. The tin-based perovskite battery prepared by the preparation method has good stability, long service life, high conversion rate and a smooth film layer; Figure 1 The process diagram of an embodiment of a method for preparing a tin-based perovskite battery is shown, and the method for preparing a tin-based perovskite battery comprises the following steps:

[0045] Step S10, providing a hole transport layer on the conductive glass substrate;

[0046] Before setting the hole transport layer, the conductive glass substrate needs to be cleaned to avoid the presence of impurities on the surface of the conductive glass substrate, which may affect the hole transport layer. At the same time, during the cleaning process, it is necessary to consider that the solvent used cannot corrode the conductive glass substrate or the hole transport layer. Specifically, in some embodiments, the solvent includes any one of acetone, isopropanol, ethanol and ultrapure water, that is, in actual application, acetone, isopropanol, ethanol, or ultrapure water can be selected as the solvent to participate in step S10. As a preferred embodiment, the solvent is ultrapure water, which contains fewer impurities and will not corrode the glass conductive substrate and the hole transport layer. It is more effective to use ultrapure water as a solvent to clean the conductive glass substrate.

[0047] In addition, after cleaning the conductive glass substrate, the conductive glass substrate needs to be treated in an ultraviolet ozone environment. The purpose is to make the hole layer solution have better wettability, thereby making the hole transport layer denser.

[0048] Furthermore, after the PEDOT:PSS (Al 4083) is spin-coated on the conductive glass substrate, an annealing treatment is required. The purpose of the annealing treatment is to accelerate the growth of crystals and the film formation speed of the hole transport layer.

[0049] When performing step S10, the following steps can be specifically performed: cleaning the conductive glass substrate with a solvent, treating it in an ultraviolet ozone environment for 15 to 20 minutes, spin coating PEDOT:PSS (Al 4083) on the conductive glass substrate at a rotation speed of 3500 to 4000 rpm, and annealing at 140 to 150° C. for 10 to 15 minutes to form a hole transport layer on the conductive glass substrate.

[0050] It should be noted that by controlling the annealing temperature and the annealing time, on the one hand, the growth rate of the crystal can be accelerated and the film formation rate of the hole transport layer can be accelerated. On the other hand, within the above-mentioned temperature range and time range, it can be ensured that the hole transport layer will not dry out and crack due to excessively high temperature and excessively long time, thereby ensuring the film formation quality of the hole transport layer.

[0051] Step S20: Send FA x MA 1-x Pb y Sn 1-y Adding carbohydrazide to the I3 solution to obtain a perovskite precursor solution;

[0052] In this embodiment, the FA x MA 1-x Pb y Sn 1-y I3 solution contains a large amount of Sn 2+ Ion, Sn 2+ The ions are extremely unstable in the air and are easily oxidized to Sn by oxides in the air (such as oxygen, etc.). 4+ ions, which makes the perovskite precursor layer unstable and reduces its service life. The structure of carbohydrazide contains amino (-NH2) and carbonyl (-C=O), which can react with Sn 2+ and Pb 2+ Interaction, avoid Sn 2+ The ions are oxidized to Sn by oxides in the air. 4+ ions, thereby increasing the battery life.

[0053] Further, in this embodiment, the amount of carbohydrazide added is effective in inhibiting Sn 2+ Ion oxidation may also have an effect. In some embodiments, the carbohydrazide and the FA x MA 1-x Pb y Sn 1-y I3 solution FA x MA 1-x Pb y Sn 1-y The volume ratio of I3 solution is (0.01-0.03):1. Specifically, in actual operation, every 100 ml of FA x MA 1-x Pb y Sn 1-y 1-3 ml of carbohydrazide is added to the I3 solution; in fact, carbohydrazide can be added according to specific circumstances. Specifically, when performing step S20, 1%, 1.5%, 2.0%, 2.5%, or 3% of carbohydrazide can be added.

[0054] Furthermore, in actual operation, FA x MA 1-x Pb y Sn 1-y The I3 solution can be prepared according to the following steps: dissolve lead iodide, stannous iodide, formamidine hydroiodide and iodomethylamine in N,N-dimethylformamide and dimethyl sulfoxide, shake under protective gas for 2 to 2.5 hours, and obtain FA x MA 1-x Pb y Sn 1-y I3 solution, to the FA x MA 1-x Pb y Sn 1-y Carbohydrazide is added to the I3 solution to obtain a perovskite precursor solution.

[0055] Furthermore, in one embodiment, the percentage concentration of lead iodide is 99.99%, the percentage concentration of stannous iodide is 99.99%, the percentage concentration of formamidine hydroiodide is 99.5%, and the percentage concentration of dimethyl sulfoxide is 99.8%.

[0056] It should be noted that in the preparation of FA x MA 1-x Pb y Sn 1-y During the preparation of I3 solution, it is necessary to prepare it under a protective gas atmosphere to avoid the oxides in the environment from 2+ Ion oxidation, specifically, in this embodiment, the protective gas is nitrogen.

[0057] Step S30, disposing a perovskite precursor layer on the hole transport layer;

[0058] Specifically, in the actual operation process, when performing step S30, the following steps can be performed: dripping a perovskite precursor solution on the hole transport layer, spin coating at a speed of 1000-1500 rpm for 10-15s, dripping an anti-solvent, and then spin coating at a speed of 3500-4000 rpm for 20-30s, and annealing at 100-110°C for 10-15min to form a perovskite precursor layer on the hole transport layer.

[0059] It should be noted that the spin coating process is divided into two spin coatings. The purpose is to add an anti-solvent, accelerate the precipitation of crystals, and accelerate the film formation of the perovskite precursor layer. Specifically, a coater is used in actual operation. First, spin coating is performed for 10 to 15 seconds, then the anti-solvent is added, and then spin coating is performed for 20 to 30 seconds to make the anti-solvent evenly dispersed.

[0060] Furthermore, in this embodiment, the anti-solvent may be chlorobenzene, ethyl acetate or a mixture of chlorobenzene and ethyl acetate.

[0061] Furthermore, the purpose of the annealing treatment is to accelerate the growth of crystals and the film formation speed of the hole transport layer.

[0062] Step S40, sequentially arranging an electron transport layer, a buffer layer and a back electrode layer on the perovskite precursor solution layer from bottom to top to obtain a tin-based perovskite battery.

[0063] When performing step S40, it can be specifically performed through the following steps: using an organic evaporator to evaporate an electron transport layer on the perovskite precursor solution layer, after cooling, using an organic evaporator to evaporate a buffer layer on the electron transport layer, after cooling, using a metal evaporator to evaporate a back electrode layer on the buffer layer to obtain a tin-based perovskite battery.

[0064] In some embodiments, the material of the electron transport layer is not limited, and can be titanium dioxide, zinc oxide, molybdenum oxide, or C60. As a preferred embodiment of this embodiment, the material of the electron transport layer is selected as C60; further, the material of the buffer layer is selected as BCP; the material of the back electrode layer is selected as Ag. Metal Ag is selected as the back electrode layer because silver has a small resistance value, which can reduce energy loss and improve the conversion efficiency of the battery.

[0065] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0066] Example 1

[0067] (1) The conductive glass substrate was cleaned with acetone and treated in a UV ozone environment for 15 minutes. PEDOT:PSS (Al 4083) was spin-coated on the conductive glass substrate at a rotation speed of 3500 rpm, and annealed at 140° C. for 10 minutes to form a hole transport layer on the conductive glass substrate.

[0068] (2) Lead iodide, stannous iodide, formamidine hydroiodide and methyl iodide were dissolved in N,N-dimethylformamide and dimethyl sulfoxide and shaken under nitrogen for 2 h to obtain FA x MA 1-x Pb y Sn 1-y I3 solution, to the FA x MA 1-x Pb y Sn 1-yI3 solution was added with carbohydrazide (the content of doped carbohydrazide was 1.5%) to obtain a perovskite precursor solution.

[0069] (3) Add a perovskite precursor solution onto the hole transport layer, spin-coat at 1000 rpm for 10 seconds, then add an anti-solvent, spin-coat at 3500 rpm for 20 seconds, and anneal at 100°C for 10 minutes to form a perovskite precursor layer on the hole transport layer.

[0070] (4) using an organic evaporator to evaporate an electron transport layer on the perovskite precursor solution layer, and after cooling, using an organic evaporator to evaporate a buffer layer on the electron transport layer, and after cooling, using a metal evaporator to evaporate a back electrode layer on the buffer layer.

[0071] Example 2

[0072] (1) The conductive glass substrate was cleaned with ethanol and treated in a UV ozone environment for 16 minutes, PEDOT:PSS (Al 4083) was spin-coated on the conductive glass substrate at a rotation speed of 3600 rpm, and annealed at 142° C. for 12 minutes to form a hole transport layer on the conductive glass substrate.

[0073] (2) Lead iodide, stannous iodide, formamidine hydroiodide and methyl iodide were dissolved in N,N-dimethylformamide and dimethyl sulfoxide and shaken under nitrogen for 2.2 h to obtain FA x MA 1-x Pb y Sn 1-y I3 solution, to the FA x MA 1-x Pb y Sn 1-y I3 solution was added with carbohydrazide (the content of doped carbohydrazide was 1%) to obtain a perovskite precursor solution.

[0074] (3) Add a perovskite precursor solution onto the hole transport layer, spin-coat at 1000 rpm for 10 s, then add an anti-solvent, spin-coat at 3500 rpm for 20 s, and anneal at 110°C for 10 min to form a perovskite precursor layer on the hole transport layer.

[0075] (4) using an organic evaporator to evaporate an electron transport layer on the perovskite precursor solution layer, and after cooling, using an organic evaporator to evaporate a buffer layer on the electron transport layer, and after cooling, using a metal evaporator to evaporate a back electrode layer on the buffer layer.

[0076] Example 3

[0077] (1) The conductive glass substrate was cleaned with ultrapure water and treated in an ultraviolet ozone environment for 17 minutes. PEDOT:PSS (Al 4083) was spin-coated on the conductive glass substrate at a rotation speed of 3500 rpm, and annealed at 144° C. for 15 minutes to form a hole transport layer on the conductive glass substrate.

[0078] (2) Lead iodide, stannous iodide, formamidine hydroiodide and methyl iodide were dissolved in N,N-dimethylformamide and dimethyl sulfoxide and shaken under nitrogen for 2.5 h to obtain FA x MA 1-x Pb y Sn 1-y I3 solution, to the FA x MA 1-x Pb y Sn 1-y I3 solution was added with carbohydrazide (the content of doped carbohydrazide was 2%) to obtain a perovskite precursor solution.

[0079] (3) Add a perovskite precursor solution onto the hole transport layer, spin-coat at 1500 rpm for 16 s, then add an anti-solvent, spin-coat at 3800 rpm for 32 s, and anneal at 100 °C for 12 min to form a perovskite precursor layer on the hole transport layer.

[0080] (4) using an organic evaporator to evaporate an electron transport layer on the perovskite precursor solution layer, and after cooling, using an organic evaporator to evaporate a buffer layer on the electron transport layer, and after cooling, using a metal evaporator to evaporate a back electrode layer on the buffer layer.

[0081] Example 4

[0082] (1) The conductive glass substrate was cleaned with isopropyl alcohol and treated in a UV ozone environment for 15 minutes. PEDOT:PSS (Al 4083) was spin-coated on the conductive glass substrate at a rotation speed of 3500 rpm, and annealed at 140° C. for 10 minutes to form a hole transport layer on the conductive glass substrate.

[0083] (2) Lead iodide, stannous iodide, formamidine hydroiodide and methyl iodide were dissolved in N,N-dimethylformamide and dimethyl sulfoxide and shaken under nitrogen for 2 h to obtain FA x MA 1-x Pb y Sn 1-y I3 solution, to the FA x MA 1-x Pb y Sn 1-y I3 solution was added with carbohydrazide (the content of doped carbohydrazide was 2.5%) to obtain a perovskite precursor solution.

[0084] (3) Add a perovskite precursor solution onto the hole transport layer, spin-coat at 1000 rpm for 10 seconds, then add an anti-solvent, spin-coat at 3500 rpm for 20 seconds, and anneal at 100°C for 10 minutes to form a perovskite precursor layer on the hole transport layer.

[0085] (4) using an organic evaporator to evaporate an electron transport layer on the perovskite precursor solution layer, and after cooling, using an organic evaporator to evaporate a buffer layer on the electron transport layer, and after cooling, using a metal evaporator to evaporate a back electrode layer on the buffer layer.

[0086] Example 5

[0087] (1) The conductive glass substrate was cleaned with acetone and treated in a UV ozone environment for 20 minutes. PEDOT:PSS (Al 4083) was spin-coated on the conductive glass substrate at a rotation speed of 4000 rpm, and annealed at 150° C. for 15 minutes to form a hole transport layer on the conductive glass substrate.

[0088] (2) Lead iodide, stannous iodide, formamidine hydroiodide and methyl iodide were dissolved in N,N-dimethylformamide and dimethyl sulfoxide and shaken under nitrogen for 2.5 h to obtain FA x MA 1-x Pb y Sn 1-y I3 solution, to the FA x MA 1-x Pb y Sn 1-y I3 solution was added with carbohydrazide (the content of doped carbohydrazide was 3%) to obtain a perovskite precursor solution.

[0089] (3) Add a perovskite precursor solution onto the hole transport layer, spin-coat at 1500 rpm for 15 seconds, then add an anti-solvent, spin-coat at 4000 rpm for 30 seconds, and anneal at 110°C for 115 minutes to form a perovskite precursor layer on the hole transport layer.

[0090] (4) using an organic evaporator to evaporate an electron transport layer on the perovskite precursor solution layer, and after cooling, using an organic evaporator to evaporate a buffer layer on the electron transport layer, and after cooling, using a metal evaporator to evaporate a back electrode layer on the buffer layer.

[0091] Comparative Example

[0092] The other steps are consistent with the preparation steps of Example 1. In step (2), when preparing the perovskite precursor solution, no carbohydrazide is added.

[0093] Performance Testing

[0094] The perovskite precursor solution prepared in step (2) of Example 1 and the perovskite precursor solution prepared in the comparative example were placed in air for 24 hours and their colors were observed. Figure 2 By comparison, it was found that the color of the perovskite precursor solution prepared in step (2) of Example 1 did not change before and after, while the color of the perovskite precursor solution prepared in the comparative example became darker, indicating that when preparing the perovskite precursor solution in Example 1, adding carbohydrazide can inhibit the Sn content of the solution. 2+ The ions are oxidized to Sn 4+ Ions, by adding carbohydrazide, can inhibit the oxidation of perovskite precursor solution, improve the stability of tin-based perovskite batteries, and extend their service life.

[0095] Take the perovskite precursor layer prepared in step (3) of Example 1 and the perovskite precursor layer prepared in step (3) of the comparative example, and obtain their SEM cross-sectional images, as shown in FIG. Figure 3 and Figure 4 Said by Figure 3 and Figure 4 It can be concluded that there are voids in the perovskite precursor layer prepared in step (3) of the comparative example, while no voids are found in the perovskite precursor layer prepared in step (3) of Example 1, indicating that the structure of the perovskite precursor layer prepared in Example 1 is more stable.

[0096] The perovskite precursor layer prepared in step (3) of Example 1 and the perovskite precursor layer prepared in step (3) of the comparative example were exposed to air for 5 days to obtain their SEM surface images. Figure 5 and Figure 6 It can be concluded that after the perovskite precursor layer without carbohydrazide is placed in the air for 5 days, the perovskite film grains have large holes, while the perovskite film grains doped with carbohydrazide are basically not damaged. Therefore, by adding carbohydrazide, the oxidation of the perovskite precursor layer can be inhibited, the stability of the tin-based perovskite battery can be improved, and the service life can be extended.

[0097] Take the tin-based perovskite battery prepared in Example 1 and the tin-based perovskite battery prepared in the comparative example, and perform IV test to obtain the IV curve. Figure 7 It can be concluded that the open circuit voltage and short circuit current of perovskite solar cells doped with carbohydrazide are greatly improved, which is attributed to the inhibition of Sn 2+The result of oxidation and regulation of nucleation and crystallization. The test method for the photoelectric conversion efficiency of perovskite solar cells: First, place the prepared battery in the solar cell test box, and link the test box with the digital source meter Keithley-2400, open the test software, fix the open circuit voltage test range between -0.1V-1.0V, and the short circuit current test range is 0mA / cm2~35mA / cm2. Then turn on the Newport solar simulator and modulate the light power to AM1.5 (equivalent to a standard sunlight). Finally, open the corresponding supporting test software to test the photoelectric conversion efficiency of the perovskite solar cell. The test environment is a clean room, and the humidity and environment are certain values.

[0098] Take the perovskite precursor layer prepared in step (3) of Examples 1 to 5 and the perovskite precursor layer prepared in step (3) of the comparative example, and obtain their SEM surface images. Figures 9 to 13 It can be concluded that the surface of the perovskite precursor layer prepared in step (3) of Examples 1 to 5 is smooth and the particle size distribution is uniform, while the surface of the perovskite precursor layer prepared in step (3) of the comparative example is rough and the particle size distribution is uneven. Figures 9 to 13 It can be concluded that the amount of carbohydrazide added will also affect the smoothness of the surface of the perovskite precursor layer. For example, when the addition amount is 3%, it will cause voids.

[0099] The perovskite precursor layer prepared in step (3) of Examples 1 to 5 and the perovskite precursor layer prepared in step (3) of the comparative example were subjected to XRD testing to obtain an XRD graph. Figure 8 It can be concluded that adding a certain amount of carbohydrazide can regulate its nucleation and crystallization process, and the crystallinity can be improved to a certain extent.

[0100] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A method for preparing a tin-based perovskite battery, characterized in that: The method comprises the following preparation steps: A hole transport layer is provided on the conductive glass substrate; To FA x MA 1-x Pb y Sn 1-y I3 solution is added with carbohydrazide to obtain a perovskite precursor solution, wherein 0 <x<1,0<y<1; Disposing a perovskite precursor layer on the hole transport layer; An electron transport layer, a buffer layer and a back electrode layer are sequentially arranged on the perovskite precursor solution layer from bottom to top to obtain a tin-based perovskite battery.

2. The method for preparing a tin-based perovskite battery according to claim 1, characterized in that: To the FA x MA 1- x Pb y Sn 1-y In the step of adding carbohydrazide to the I3 solution to obtain a perovskite precursor solution, the carbohydrazide and the FA x MA 1-x Pb y Sn 1-y The volume ratio of I3 solution is (0.01~0.03):

1.

3. The method for preparing a tin-based perovskite battery according to claim 1, characterized in that: To the FA x MA 1- x Pb y Sn 1-y The steps of adding carbohydrazide to the I3 solution to obtain a perovskite precursor solution include: Lead iodide, stannous iodide, formamidine hydroiodide and methyl iodide were dissolved in N,N-dimethylformamide and dimethyl sulfoxide, and shaken for 2 to 2.5 hours under protective gas to obtain FA x MA 1-x Pb y Sn 1-y I3 solution, to the FA x MA 1-x Pb y Sn 1-y Carbohydrazide is added to the I3 solution to obtain a perovskite precursor solution.

4. The method for preparing a tin-based perovskite battery according to claim 3, characterized in that: The protective gas includes nitrogen.

5. The method for preparing a tin-based perovskite battery according to claim 1, characterized in that: The step of providing a perovskite precursor layer on the hole transport layer comprises: A perovskite precursor solution is dripped onto the hole transport layer, and the solution is spin-coated at a speed of 1000 to 1500 rpm for 10 to 15 s, an anti-solvent is dripped, and the solution is spin-coated at a speed of 3500 to 4000 rpm for 20 to 30 s. The solution is annealed at 100 to 110° C. for 10 to 15 min to form a perovskite precursor layer on the hole transport layer.

6. The method for preparing a tin-based perovskite battery according to claim 5, characterized in that: The anti-solvent includes chlorobenzene and / or ethyl acetate.

7. The method for preparing a tin-based perovskite battery according to claim 1, characterized in that: The step of providing a hole transport layer on a conductive glass substrate comprises: The conductive glass substrate is cleaned with a solvent, treated in an ultraviolet ozone environment for 15 to 20 minutes, PEDOT:PSS (Al 4083) is spin-coated on the conductive glass substrate at a rotation speed of 3500 to 4000 rpm, and annealed at 140 to 150° C. for 10 to 15 minutes to form a hole transport layer on the conductive glass substrate.

8. The method for preparing a tin-based perovskite battery according to claim 5, characterized in that: The solvent includes any one of acetone, isopropanol, ethanol and ultrapure water.

9. The method for preparing a tin-based perovskite battery according to claim 1, characterized in that: The steps of sequentially arranging an electron transport layer, a buffer layer and a back electrode layer from bottom to top on the perovskite precursor solution layer include: An electron transport layer is evaporated on the perovskite precursor solution layer using an organic evaporator. After cooling, a buffer layer is evaporated on the electron transport layer using an organic evaporator. After cooling, a back electrode layer is evaporated on the buffer layer using a metal evaporator to obtain a tin-based perovskite battery.

10. The method for preparing a tin-based perovskite battery according to claim 1, characterized in that: The material of the electron transport layer includes C60; and / or, The material of the buffer layer includes 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline; and / or, The material of the back electrode layer includes Ag.

Citation Information

Patent Citations

  • Full-printing mesoscopic perovskite solar cell taking aniline or azine ring as additive and preparation method thereof

    CN111146344A

  • Tin-based perovskite thin film as well as preparation method and application thereof

    CN113948642A